Samoa : Request for Disbursement Under the Rapid Credit Facility-Press Release; Staff Report; and Statement by the Executive Director for Samoa. - International Monetary Fund. Asia and Pacific Dept. (Washington, D.C. : International Monetary Fund, 2020)
This paper discusses Samoa's Request for Disbursement Under the Rapid Credit Facility. Samoa has shown resilience to multiple past economic shocks, underpinned by the authorities' strong commitment to support the economy, and financial assistance provided by the international community. The global coronavirus disease 2019 pandemic has exacerbated the impact of the measles outbreak of late-2019 on Samoa's economy. The border closure, combined with a sudden stop of tourist arrivals and decline in remittances, has led to a precipitous fall in two vital sources of foreign earnings and resulted in an urgent balance of payments need. Beyond the immediate response, the authorities will continue to implement structural reforms, with policies appropriately balanced between safeguarding debt sustainability and promoting economic growth. They also need to continue their efforts to enhance spending efficiency, strengthen social protection programs and safety nets, further improve tax administration, strengthen public financial management, and safeguard financial stability. Addressing vulnerability to climate change remains a key medium-term challenge to create a fiscal buffer.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet